2010
DOI: 10.1111/j.1476-5381.2010.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

A2b adenosine receptors can change their spots

Abstract: Recently, a central role for the A2b adenosine receptor in a variety of cardiovascular functions including inflammation, erectile function, coronary artery dilation, asthma and cardioprotection has been demonstrated. Despite this evidence, the low-affinity A2b adenosine receptor is still poorly understood. This receptor appears to be very promiscuous in its coupling. In most tissues, it couples to Gs much like its cousin, the A2a adenosine receptor, but in mast cells and now, most recently, in cardiac fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
(15 reference statements)
0
21
0
Order By: Relevance
“…One possibility would be a direct heteromerisation between A 2B R and A 1 R, given that A 2B R can heteromerise with different membrane proteins such as receptors (Corset et al ., ; Moriyama & Sitkovsky, ) and enzymes (Antonioli et al ., ) and A 1 R can also form dimers with different G‐protein‐coupled receptors (Gines et al ., ; Ciruela et al ., ; Kamikubo et al ., ). An alternative would be an ability of A 2B R to trigger an intracellular cross talk through its diverse G‐protein coupling (Ryzhov et al ., ; Cohen et al ., ; Liu et al ., ) to functionally desensitise A 1 R (Ciruela et al ., ; Nie et al ., ; Hashimi et al ., ; Lopes et al ., ), in a manner analogous to the ability of A 2B R to control ion channels (Garção et al ., ), G protein coupled receptors (Feoktistov & Biaggioni, ; Conde et al ., ) or growth factor receptors (Corset et al ., ). Further studies will be required to clarify the mechanism underlying the ability of A 2B R to functionally desensitise A 1 R in nerve terminals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility would be a direct heteromerisation between A 2B R and A 1 R, given that A 2B R can heteromerise with different membrane proteins such as receptors (Corset et al ., ; Moriyama & Sitkovsky, ) and enzymes (Antonioli et al ., ) and A 1 R can also form dimers with different G‐protein‐coupled receptors (Gines et al ., ; Ciruela et al ., ; Kamikubo et al ., ). An alternative would be an ability of A 2B R to trigger an intracellular cross talk through its diverse G‐protein coupling (Ryzhov et al ., ; Cohen et al ., ; Liu et al ., ) to functionally desensitise A 1 R (Ciruela et al ., ; Nie et al ., ; Hashimi et al ., ; Lopes et al ., ), in a manner analogous to the ability of A 2B R to control ion channels (Garção et al ., ), G protein coupled receptors (Feoktistov & Biaggioni, ; Conde et al ., ) or growth factor receptors (Corset et al ., ). Further studies will be required to clarify the mechanism underlying the ability of A 2B R to functionally desensitise A 1 R in nerve terminals.…”
Section: Discussionmentioning
confidence: 99%
“…The other adenosine receptors, namely adenosine A 2B receptors (A 2B R), have low expression levels in the brain (Dixon et al ., ). A 2B R are recognised as G s/q ‐protein‐coupled receptors (Feoktistov & Biaggioni, ), although they can interact with different G‐protein‐coupled receptors to recruit other G‐proteins (Ryzhov et al ., ; Cohen et al ., ; Liu et al ., ). Our knowledge about A 2B R mostly stems from their peripheral roles controlling cardiac myocite contractility, intestinal tone, asthma, inflammation, cancer and diabetes (Feoktistov & Biaggioni, ; Headrick et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In mast cells 57 and cardiac fibroblasts 58 A 2B receptors couple to protein kinase C, and it is conceivable that this also occurs in HCASMCs. However, if so this would probably not contribute to inhibition of HCASMC proliferation because our previous studies suggest that PKC is involved in stimulating, rather than inhibiting, VSMC proliferation 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported that A 2b promotes T reg -cell differentiation and limits inflammatory injury 120 . A 2b signals by multiple pathways; not only does A 2b increase cAMP via coupling to G s proteins but they might also signal via G q and G i proteins, thereby explaining their cAMP-independent effects on generation of IL-6 121 .…”
Section: The Adaptive Immune Systemmentioning
confidence: 99%